1996
DOI: 10.1111/j.1365-2044.1996.tb04641.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in anaesthetic care resulting from a critical incident reporting programme

Abstract: The r d e of an anaesthetic incident reporting programme in improving anaesthetic safety was studied. The programme had been running for 4 to 5 years in three large hospitals in Hong Kong and more than 1000 incidents have been reported. The number of reports being made and frequency of the various categories of incident reported, did not alter during the study period. Sixty nine percent of incidents were considered to be preventable. Human error contributed to 76% of incidents and violations of standardpractic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 17 publications
(2 reference statements)
0
32
1
1
Order By: Relevance
“…Human error in our study was a factor in 55% of incidents which is lower than that reported in the anaesthesia literature [1,4,18,20,21]. In the critical care literature an incidence of between 66% and 80% has been reported [7,11,17].…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Human error in our study was a factor in 55% of incidents which is lower than that reported in the anaesthesia literature [1,4,18,20,21]. In the critical care literature an incidence of between 66% and 80% has been reported [7,11,17].…”
Section: Discussioncontrasting
confidence: 48%
“…Critical incident reporting is a well established QA in clinical anaesthesia [1][2][3][4][5][6]. However, there are significant differences regarding patient management between the operating theatre and the ICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of improvement in anesthetic care resulting from a critical incident reporting programme have also been studied by Short et al 28 They found no change in ampoule or syringe swaps, or general pharmacological incidents after increased awareness of problems at QA meetings and written reports, using a qualitative study design. It seems that the addition of 'visual and mental cues' is not strong enough alone to correct the mistakes.…”
Section: Impact Of Interventionmentioning
confidence: 99%
“…Critical incident analysis was introduced to anaesthesia practice by Cooper et al [1] in 1978 and is now firmly established. This analysis can be used for auditing work practice, for correction of factors contributing to the incident and for identification of recurrent problems [2]. To date, the largest published series has been reported by the Australian Incident Monitoring Study (AIMS) [3].…”
mentioning
confidence: 99%